Developing, testing and validating template of Modified Workload Indicators of Staffing Need (m-WISN) for Oral Health Division (OHD), Ministry of Health Malaysia (MOH) - Che Musa, Muhd Firdaus (2017)
Globally there is an increasing recognition that the human resources for health are integral to the success and overall performance of the health system. In this regards, the WHO states that health workers comprise of “all people engaged in actions whose primary intent is to enhance health”, and there is “no health without a workforce”. The Workload Indicators of Staffing Need (WISN) is a projection tool introduced by the WHO and it is still highly favoured ad used to calculate workforce requirement in a given facilities across the world after its publication in 1998. There is a need for research informed action in relation to understand workforce influences and workloads, examining their potential implications and the shape of the future workforce in relation to population need. Therefore, in this study, the original WISN was revised and reviewed for Malaysian context. As middle to high-income country, Malaysia has increased the number of dental schools in the last decade to ensure that there are sufficient health workers to meet the needs and demands of the population. As the volume of dentists entering the workforce has increased, concerns about the long-term implications of dental education policies and how this expensively trained dental workforce will be holistically utilised along with other dental; including dental specialists in the future are emerging. The Ministry of Health Malaysia (MOH) has used various methodologies over the years to plan and project human resources for health services. The restraints and instability in the country’s economy and distribution of workforce’s skills and the lack of human resources in health services have caused difficulties in the attempt to develop a better method to plan and place various types of workforce at different facilities. In 2015, the Oral Health Division set the dentist to population ratios to 1: 3000 as the basis for calculating staff requirements that will be provided through 13 operating dental schools that have been approved under the current local dental moratorium policy. In mean times, several WISN studies have been successfully conducted and documented in different countries; focusing on the processes undertaken, challenges faced and lessons learned. This report, which complements the revised WISN, user’s manual and provides examples of how the WISN method has been applied in the unique context in Malaysia in attempt to document the experience of the Malaysian Oral Health Division (OHD) in developing, testing and validating its own modified WISN (m-WISN) template. The WISN tool provides a methodology that could, if followed accurately, produce evidence based results that can be understood by all relevant stakeholders and partners in the country, with the Ministry of Health Malaysia as the preferred lead institution. The initiative to use WISN at the dental level in Malaysia came from a medical counterpart at MOH. In this light, the implementation of the WISN tool is more likely to succeed when leaders in both primary setting, as well as specialists at hospital and non-hospital based settings are involved in capacity building from the start as capacity-building is an integral and crucial part of the WISN implementation strategy as recommended by the WHO. Thus, capacity-building should adopt a bottom-up, partnership-based approach and in most if not all cases, national capacity building demands external support in form of financial and local human resources institutions. A briefing session was first conducted prior to this report to enable policy-makers or the steering committee to make a final decision on whether to proceed with the modified template of WISN or not. Partial involvement of the steering committee will lead to non-acceptance of the method. A technical task force was then created to ensure the efficient execution of this project. It also worth to note even though report focuses mainly on dental facilities offered at Ministry of Health Malaysia where the WISN studies were conducted, the development and the use of WISN depend on the needs of the country through reviewing the staffing norms and standards for different health facilities. In the case for Malaysia, primary care setting in both the hospital and non-hospital based specialist clinics has been tested to improve its face and content validity. The WISN can help ensure that the provider could supply the right human resources, with the right skills in the right place and time. WISN provides an accurate indication of the staffing requirements based on actual workloads and expert professional opinion and its results can be used in the determination of staffing norms and standards. WISN results can also assist in improving many other types of decision making related to health workforce planning and management, such as rationalising the distribution of current staff, aligning task allocation among cadres, reducing workload pressure and increasing the quality of current health services. Consequently, WISN results can be used to evaluate staffing capacity and capability over the previous year as well as to forecast the likely short term staffing requirements of facilities based on future workloads. The results can also be used to assess the staffing distribution in similar types of health facilities and identify which health facilities face a shortage or surplus of staff in relation to the workload, and estimate the size of the staffing deficit or surplus. Such analysis can also help Malaysia to estimate how many additional or in some cases fewer staff required to optimise the total staff ratio in all facilities to the level that corresponds to the existing staffing and standards. In addition, WISN can indicate the staffing consequences arising from creating a new staff category to undertake specific functions addressed by existing staff categories. The WISN tool is not intended for one-off use. Based on its design, it is hoped that countries or facilities will mainstream the tool into the management processes of health workforce planning and implementation. The maximum use of the tool can be ensured by building capacity at the national and lower levels. In this light, the Malaysian experience shows that the WISN method can be used by health workers, even those working at the marginal level. These health workers found it highly motivating that the WISN results they had calculated were used by decision makers to improve the staffing situation. On the other hand, the WISN method is not the only method or tool to improve the planning and management of human resources. WISN could also be integrated with other relevant human resource tools to build more robust human resource systems. These case studies are intended to encourage readers to apply the WISN method in their own settings and at the same time considering what other tools that could be used to complement WISN.